A multi-faceted review of wind turbine optimization techniques: Metaheuristics and related issues - Rezk, Hegazy; Olabi, Abdul Ghani; Wilberforce, Tabbi; Sayed, Enas Taha (International Journal of Thermofluids, 2025)
Wind energy conversion is increasingly attracting attention as a viable renewable energy source due to its ability to satisfy electricity requirements while considering economic and environmental factors. To get the highest possible power harvesting from wind, optimization approaches are used to address a range of issues about wind energy. This article comprehensively reviews the current optimization state for wind energy systems and examines the use of metaheuristic optimization algorithms. Metaheuristic optimization algorithms combine fundamental heuristic concepts with approximation approaches to effectively explore and utilize research space. They seek ideal or almost ideal results and are based on previous experience. Their applications in the context of wind energy will be investigated in this paper. First, the basics of the wind turbine conversion systems, including the models and classifications, are presented. Then, the main problems related to wind energy are reported. These problems include aerodynamic design, structural design, damage detection, optimal onshore and offshore locations, control optimization, and wind energy assessment. Next, an analysis of the use of metaheuristic optimization algorithms will be provided, followed by an exhaustive study and evaluation of the latest papers published in Scopus that solve problems related to wind energy. Finally, recommendations and future trends are discussed. This review will help scholars broaden their perspectives to investigate potential applications within this subject and beyond.